2020
DOI: 10.2147/ndt.s254065
|View full text |Cite
|
Sign up to set email alerts
|

<p>Lack of Association Between <em>PLA2G6</em> Genetic Variation and Parkinson’s Disease: A Systematic Review</p>

Abstract: Background: The phospholipase A2 Group 6 (PLA2G6, also known as PLA2, PARK14, and iPLA2) gene encodes a group VIA calcium-independent phospholipase A2. Genetic polymorphism of PLA2G6 has been indicated to be involved in conferring susceptibility for Parkinson's disease (PD), whereas conclusive results have not been obtained. Thus, we intended to conduct a systematic review to determine if PLA2G6 genetic variation confers a greater susceptibility to PD. Methods: All case-control studies that investigated the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Increased alpha-synuclein expression appears to be a direct consequence of iPLA2 deficiency [211]. Yet, several studies examined the association between PLA2G6 genetic variants and PD arriving at the conclusion that monoallelic PLA2G6 variants do not increase PD risk [212][213][214][215]. Patient-derived iPCs with biallelic PLA2G6 mutation differentiated into dopaminergic midbrain neurons exhibited signs of increased endoplasmic reticulum stress.…”
Section: Neurodegenerations With Brain Iron Accumulation (Nbia) Groupmentioning
confidence: 99%
“…Increased alpha-synuclein expression appears to be a direct consequence of iPLA2 deficiency [211]. Yet, several studies examined the association between PLA2G6 genetic variants and PD arriving at the conclusion that monoallelic PLA2G6 variants do not increase PD risk [212][213][214][215]. Patient-derived iPCs with biallelic PLA2G6 mutation differentiated into dopaminergic midbrain neurons exhibited signs of increased endoplasmic reticulum stress.…”
Section: Neurodegenerations With Brain Iron Accumulation (Nbia) Groupmentioning
confidence: 99%
“…There are conflicting reports about the role of variants in PLA2G6 and risk of PD, with some demonstrating an association (Liu et al 2020a , b ) and others not (Liu et al 2020a , b ). However, a study using cells obtained from idiopathic PD patients demonstrated deficient activity of iPLA2, the protein product of PLA2G6 (Zhou et al 2016 ), and it has been reported to be located within Lewy bodies of idiopathic PD cases (Miki et al 2017 ).…”
Section: Implications For Idiopathic Lewy Body Diseasementioning
confidence: 99%